A high-efficiency and high-precision automatic 3D scanning system for industrial parts based on a scanning path planning algorithm. (November 2022) - Zong, Yulong; Liang, Jin; Pai, Wenyan; Ye, Meitu; Ren, Maodong; Zhao, Jianbo; Tang, Zhengzong; Zhang, Jiyao
Highlights: The automated 3D scanning system proposed in this research realizes the automatic calculation of scanning paths and the automatic splicing of scanning data, which greatly improves scanning efficiency and greatly reduces the difficulty of scanning complex objects. This research proposes a virtual scanning principle, which accurately defines the conditions that a point on the surface of an object can be scanned by a binocular scanner, to provide a theory for the calculation of the optimal viewpoint in the scanning path. In addition, the virtual scanning principle has strong expansibility and can be easily adapted to different scanners. This research proposes an automated 3D scanning path planning algorithm based on virtual scanning, which can realize the calculation of the global viewpoint of the measured object with a 3D digital model and the planning of the execution path, and the effectiveness of the algorithm and the accuracy greatly improves the technical level in the field of automated 3D scanning path planning. This research proposes two splicing methods of scan data, one is a photogrammetry-based marker point stitching method with high accuracy, and the other is a high-efficiency mechanical stitching method based on system calibration results. The corresponding method can be selected according to different usage requirements. In addition to the automated 3D scanning of complex parts, the calibration algorithm of the automated system proposed in this study has a good reference for automated applications such as automated welding and automated grabbing using robotic arms. Abstract: To achieve high-precision and high-efficiency 3D scanning of industrial parts, this research proposes an automated 3D scanning system based on path planning algorithms, in which the 3D scanning sensor is realized based on the principle of raster projection. The proposed automated scanning system is composed of a robotic arm, a 3D scanner, and a turntable to achieve a complete 3D scanning of the object to be measured. More precisely, this paper proposes a virtual 3D scanning principle, which can accurately determine whether a certain point on the CAD model can be scanned by a viewpoint. Further, this paper proposes a path planning algorithm based on the virtual 3D scanning principle, which can calculate the optimal scanning path required to scan the object according to the CAD model of the scanned object. Furthermore, to ensure the accuracy of the system, a high-precision system calibration method is proposed to establish the accurate positional relationship between various parts of the system. Firstly, this research proposes a camera calibration algorithm based on close-range photogrammetry, which can calculate the high-precision interior and exterior orientation parameters of the camera, and apply the method of calculating camera external parameters to the hand-eye calibration, making the accuracy of hand-eye calibration is also improved accordingly. In addition, this research proposes a photogrammetry-based projector calibration algorithm to determine the positional relationship between the projector and the camera in the 3D scanner, and a turntable calibration method to determine the positional relationship between the rotation center of the turntable and the camera. Eventually, according to different usage requirements, two 3D scanning data splicing methods are proposed. One is a high-efficient automatic splicing method based on the results of system calibration without pasting mark points, and the other is a high-precision data splicing method based on photogrammetry. Experimental results demonstrate that this system has higher accuracy and better performance in system calibration, scanning path calculation, and multi-view scanning data splicing.